Предмет:
МатематикаАвтор:
анонимДля функции y = f (x) найдем первообразную.
f (x) = -1/(6 * x + 1)^2.
F (x) = ∫(-1/(6 * x + 1)^2 dx = ∫ -(6 * x + 1)^(-2) dx = - ∫ (6 * x + 1)^(-2) dx = -1/6 ∫ (6 * x + 1)^(-2) d (6 * x) = -1/6 ∫ (6 * x + 1)^(-2) d (6 * x + 1) = -1/6 * (6 * x + 1)^(-2 + 1)/(-2 + 1) + C = -1/6 * (6 * x + 1)^(-1)/(-1) + C = 1/6 * (6 * x + 1)^(-1) + C = 1/(6 * (6 * x + 1)) + C;
Значит, первообразная функции f (x) = -1/(6 * x + 1)^2 равна F (x) = 1/(6 * (6 * x + 1)) + C.
Автор:
shelby98Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть